INNOVATIVE DIGITAL LEARNING MEDIA TO ENHANCE STUDENT ENGAGEMENT AND LEARNING OUTCOMES IN ELEMENTARY SCHOOLS - anggitarachmawati (Schola, 2025)
This study examines the potential and implementation of digital learning media in improving student engagement, motivation, and learning outcomes in elementary schools. With the rapid advancements in information and communication technology, integrating digital media such as educational applications, interactive videos, simple virtual reality (VR), and educational games has become increasingly relevant to accommodate the learning characteristics of elementary school students in the digital age. This article analyzes various effective types of digital media, pedagogical strategies for their application, and their positive impact on enhancing conceptual understanding, developing 21st-century skills, and fostering an innovative learning environment. The method used is a comprehensive literature review of relevant prior studies and theoretical frameworks. The findings indicate that the appropriate utilization of digital learning media can transform the learning paradigm into a more dynamic, personalized, and effective experience for elementary school students.